Development of Orally Bioavailable Peptides Targeting an Intracellular Protein: From a Hit to a Clinical KRAS Inhibitor - Tanada, Mikimasa; Tamiya, Minoru; Matsuo, Atsushi; Chiyoda, Aya; Takano, Koji; Ito, Toshiya; Irie, Machiko; Kotake, Tomoya; Takeyama, Ryuuichi; Kawada, Hatsuo; Hayashi, Ryuji; Ishikawa, Shiho; et al. (Journal of the American Chemical Society, 2023)
Cyclicpeptides as a therapeutic modality are attractinga lotof attention due to their potential for oral absorption and accessibilityto intracellular tough targets. Here, starting with a drug-like hitdiscovered using an mRNA display library, we describe a chemical optimizationthat led to the orally available clinical compound known as LUNA18,an 11-mer cyclic peptide inhibitor for the intracellular tough targetRAS. The key findings are as follows: (i) two peptide side chainswere identified that each increase RAS affinity over 10-fold; (ii)physico-chemical properties (PCP) including Clog P can be adjusted by side-chain modification to increasemembrane permeability; (iii) restriction of cyclic peptide conformationworks effectively to adjust PCP and improve bio-activity; (iv) cellularefficacy was observed in peptides with a permeability of around 0.4x 10(-6) cm/s or more in a Caco-2 permeabilityassay; and (v) while keeping the cyclic peptide's main-chainconformation, we found one example where the RAS protein structurewas changed dramatically through induced-fit to our peptide side chain.This study demonstrates how the chemical optimization of bio-activepeptides can be achieved without scaffold hopping, much like the processesfor small molecule drug discovery that are guided by Lipinski'srule of five. Our approach provides a versatile new strategy for generatingpeptide drugs starting from drug-like hits.